Profile training in the system of general secondary education in Kazakhstan - Uvaliyeva, S.K.; Kamalova, G.B.; Damekova, S.K.; Kornilov, V.S. (KSU Publ., 2018)
The article deals with the modernization of the structure of the secondary educational system in Kazakhstan, based on the phased introduction of the updated school education content in the framework of 12-year education with the transition to profile education at the senior level of education. The definition of two leading concepts of profile education is given, such as differentiation and individualization. The concept of modernization of Kazakhstan education at the senior stage of the 12-year secondary school provides for profile training, the task is to form a system of specialized training (profile training) in the general upper secondary school, focused on individualization of education and specialization of pupils, which includes the real needs of the labor market. The leading principle of building a modern learning process is differentiation, which has become a means of solving the problem of satisfying the interests, vocations and needs of schoolchildren, a stimulus for the development of their creative activity. The authors list the goals and objectives of profile training within the system of secondary education in Kazakhstan. The stages of formation and development of profile differentiation of training are considered. The definition of the phenomenon of «profile education» by various authors is being traced.
Казақстандағы жалпы білім беру жүйесінде бейіндік оқыту
Профильное обучение в системе общего среднего образования в Казахстане
Keywords: updating content of education; 12-year training; profile education; general secondary education; differentiation; individualization